Akutní stav národního programu skríninku rakoviny prsu v Ceské republice - Svobodník, A; Danes, J; Skovajsová, M; Bartonková, H; Májek, O; Klimes, D (Casopis lekaru ceskych, 2007)
Czech National Breast Cancer Screening Program started in September 2002. Currently, a total of 59 accredited screening centres are involved in the program. Central data management and statistical processing of the data is performed. During the period of July 2003-December 2005 a total of 646,056 women were screened and 2,926 breast cancer cases were detected. A total of 2666 (91.1 %) cancer cases were invasive. Of these, 855 (32.1 %) were < or = 10 mm in size and 1624 (60.9 %) were node negative. A high rate of detection of early stages of the disease is the main objective of the screening process and a good indicator of long-term decrease in mortality rates. The central system of data management is based on annual data analysis. This system is in line with international standards for such systems.
Keywords: nádory prsu; Mammography; plošný screening; senioři; mamografie; ženské pohlaví; Česká republika; lidé středního věku; ultrasonografie prsů; Breast Neoplasms; Czech Republic; Mass Screening; Middle Aged; Female; lidé; Humans; Aged; Ultrasonography, Mammary